The efficiency implications of financial conglomeration - Ville Mälkönen (Bank of Finland, 2004)
This paper studies the competitive and efficiency implications of financial conglomeration driven by cost-efficiency gains in monitoring credit and insurance customers.The analysis shows that conglomeration is conducive to tougher competition in the credit market and increases profit in insurance.The aggregate profit in the financial sector does not increase, because the conglomerates pass the cost-efficiency gains on to the borrowers in full.More competitive market for financial services also reduces the aggregate risk in the financial markets, indicating that capital requirements in both sectors should be lower in the presence of financial conglomerates
URN:NBN:fi:bof-20140807255
Keywords: G21; G22; G38; L40; 330; financial conglomerates; banking; insurance; capital regulation